New International Dictionary of New Testament Theology and Exegesis. Volumen V - Silva, Moisés (Zondervan, 2014)
Offering a wealth of background and information on the meaning of Greek words in the New Testament—as well as related usage in classical Greek sources, the Septuagint, Jewish literature, and more—this important tool offers the following features: